Search for new resonances decaying to a W or Z boson and a Higgs boson in the ℓ+ℓ−bb¯, ℓνbb¯, and νν¯bb¯ channels with pp collisions at s=13 TeV with the ATLAS detector - M. Aaboud; G. Aad; B. Abbott; J. Abdallah; O. Abdinov; B. Abeloos; R. Aben; O.S. AbouZeid; N.L. Abraham; H. Abramowicz; H. Abreu; R. Abreu; et al. (Physics Letters B, 2017)
A search is presented for new resonances decaying to a W or Z boson and a Higgs boson in the ℓ+ℓ−bb¯, ℓνbb¯, and νν¯bb¯ channels in pp collisions at s=13 TeV with the ATLAS detector at the Large Hadron Collider using a total integrated luminosity of 3.2 fb−1. The search is conducted by looking for a localized excess in the WH/ZH invariant or transverse mass distribution. No significant excess is observed, and the results are interpreted in terms of constraints on a simplified model based on a phenomenological Lagrangian of heavy vector triplets.